Sezónní variabilita izokinetické síly flexoru a extenzoru kolene u fotbalistu kategorie U19 - Lehnert, M.; Chvojka, P.; Psotta, R. (Telesna Kultura, 2015)
BACKGROUND: Muscle strength is an important factor in soccer from the performance and health perspective. There is a lack of knowledge about changes in muscle strength of the knee flexors and extensors and their ratios during annual training cycle. OBJECTIVES: The aim of this study was to evaluate the seasonal variability of the observed parameters of isokinetic strength of the knee flexors and extensors in soccer players, U19, from the performance and health perspective. METHODS: The strength of the knee flexors and extensors was measured in players U19 category (n = 9; the average age 18.5 ±0.4 years) on the isokinetic dynamometer IsoMed 2000 in angular velocity 60° × s-1. Measurement was performed in concentric/concentric and excentric/excentric mode of muscle action at the beginning of the winter preparatory period, at the end of the preparatory period and at the end of the spring competitive period. Monitored parameters were absolute peak torque (PT), conventional H/Q ratio (H/QCON), functional H/Q ratio (H/QFUN) and functional H/Q ratio in range 10-30° of knee flexion (H/QFUN_10-30). RESULTS: Significant change in PT (p < .05) was noted only in cases of the knee extensors of the nondominant leg in the concentric mode. The evaluation of imbalance of the knee flexors and extensors by H/QCON and H/QFUN ratios did not show any significant changes, but there was found a significant decrease of the H/QFUN_10-30 ratio in the dominant leg between measurements at the beginning and at the end of the winter preparatory period. CONCLUSIONS: The results of the current study indicate that throughout the monitored periods of the annual training cycle desirable changes in knee flexors and extensors strength did not occur. The values suggest the disruption of the dynamic stabilization of the knee joint and increase in injury risk. Different dynamics of the three observed ratios confirmed that they provide different information about the physical fitness of players. For this reason we recommend the use of all of them in strength diagnostics in soccer.